Address to the United Nations Conference on Trade and Development, Santiago, Chile, April 14, 1972 - McNamara, Robert S. (World Bank, Washington, DC, 2020)
Robert S. McNamara, President of the World Bank Group, believes that the state of development in most of the developing world today is unacceptable. It is unacceptable, but not because there has not been progress. There has been the total economic growth, measured in Gross National product (GNP) terms, for the developing countries during the first development decade was impressive. For some of these countries it was the most successful decade measured in these gross economic terms in their history. Finally, if the state of development today is unacceptable, we must not waste time looking for villains. Rather, the entire international development community must promptly move forward with practical measures which are conceptually sound, financially feasible, and which can command the requisite public support. He spoke about income distribution, official development assistance efforts, debt problems, trade expansion, and the World Bank’s Five-Year Program.